INVESTIGATING BARRIERS PRINCIPALS ENCOUNTER EXECUTING RIGHTSIZING AS A WHIP FOR TEACHERS IN SCHOOLS - Saltiel Khololo Collen Mataboge (CV. RADJA PUBLIKA, 2024)
The purpose of this conceptual paper is to investigate the barriers school principals encounter when executing rightsizing as a punishment for teachers. The main question guiding the study is: What are the challenges and implications of utilizing rightsizing as a punishment in schools? Employing a qualitative approach, the study reviews recent scholarly literature to explore the complexities of this issue. An interpretive paradigm is adopted to gain deeper insights into the perceptions surrounding rightsizing as a disciplinary strategy. Findings suggest that using rightsizing in this manner negatively affects teacher morale, job satisfaction and the general school environment fostering notions of inequity and lack of administrative support. This study contributes to existing knowledge by highlighting the adverse effects of punitive rightsizing and informing policy and leadership practices. Limitations include potential biases in the reviewed literature and the case study's context which may not be applicable to all settings.